2002
DOI: 10.1002/1521-396x(200205)191:1<235::aid-pssa235>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Polycrystalline State and Partial Dy Substitution on the Superconducting Properties of YBCO

Abstract: The influence of the quasi-equal partial substitution of non-magnetic (Y 3+ )/magnetic (Dy 3+ ) ions in YBa 2 Cu 3 O 7--y on the superconducting properties of the material has been investigated. To minimize the influence of the stress field induced by lattice mismatch, Dy-substituted YBa 2 Cu 3 O 7--y was studied because Y 3+ and Dy 3+ ions have similar ionic radii. The investigation was performed on polycrystalline and powder samples with general formula Dy x Y 1--x Ba 2 Cu 3 O 7--y (x ¼ 0.4-0.6). Higher magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…The first one is the modification of the microstructure in order to obtain fundamental information related to the possible mechanisms, and the second one is to improve its physical characteristics. In order to improve the superconducting properties of Y123, rare earth element doping of the Y site has been investigated [16][17][18][19][20][21][22][23]. It was shown that substitutions at the Y and Ba sites did not generate any discernible effect, while substitution at the Cu and O sites had significant effects on the superconducting properties of cuprates [24].…”
Section: Introductionmentioning
confidence: 99%
“…The first one is the modification of the microstructure in order to obtain fundamental information related to the possible mechanisms, and the second one is to improve its physical characteristics. In order to improve the superconducting properties of Y123, rare earth element doping of the Y site has been investigated [16][17][18][19][20][21][22][23]. It was shown that substitutions at the Y and Ba sites did not generate any discernible effect, while substitution at the Cu and O sites had significant effects on the superconducting properties of cuprates [24].…”
Section: Introductionmentioning
confidence: 99%
“…It was also reported that the sample Dy 0.6 Y 0.4 Ba 2 Cu 3 O 7−δ has the higher losses and J c at T = 4.2 K in comparison with DyBCO [16].…”
Section: Introductionmentioning
confidence: 88%
“…We note that Dy substitution increased the critical temperature T c at certain doping rates (when x is 0.2, 0.4, 0.6). Most researchers have found that their Dy-substituted samples show a decrease in T c by using a resistive [4,16] and inductive [11,17] method. The substitution of Dy 3+ ions for Y 3+ ions possibly introduces difference in the electronic state in the CuO 2 plane and affects the transition temperature T c .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations